Kallmann syndrome and deafness: an uncommon combination: A case report and a literature review - Nader Salama (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Kallmann syndrome (Kal S) is an isolated form of hypogonadotrophic hypogonadism in combination with a defect in smell sensation. Depending on the genetic form of the disease, a number of non-reproductive, non-olfactory abnormalities may also be existent. In the present report, we describe a male with Kal S associated with hearing loss, and the successful treatment of his sexual and reproductive defects. Case: A 23-year-old Caucasian man presented with a lifelong lack of erection and ejaculation. The patient reported also anosmia combined with loss of hearing ability. A diagnostic work-up identified the presence of Kal S associated with sensorineural hearing loss. Administration of gonadotrophins regained the erection and a viable-sperm containing ejaculation. Conclusion: Lack of erection and ejaculation are important components of delayed puberty which could lead to diagnosis of Kal S. The existence of a hearing impairment in the reported patient makes the recommendation to screen the hearing ability in Kal S of utmost importance